Budistična meditacija vipasana v kontekstu new agea - Korun, Maja (Etnolog. Nova vrsta (Ljubljana), 2009)
This article tries to situate the Buddhist meditation called Vipassana in a New Age context on the basis of recollections and acknowledgements of the lives of a certain target group of people. With the introduction of Vipassana and the New Age phenomenon along with arguments from psychology, this article emphasis and exposes the way these individuals deal with existential problems in life, employing various modes and mainly spirituality, which becomes a formof alternative psychology. In its original context, Vipassana helps a more efficient integration and functioning of individuals inside a society, however, in a relatively new environment (Europe), it is reinterpreted and leads to an estrangement from duties imposed and expected of us.
Keywords: Korun, Maja; ethnology; etnologija; terensko delo; verovanje; new age; meditacija; vipasana; psihologija; psychology